2015
DOI: 10.4088/jcp.13m08812
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Utilizing Plasma <em>MiRNA107</em> and <em>BACE1</em> Messenger RNA Gene Expression for Clinical Diagnosis of Amnestic Mild Cognitive Impairment

Abstract: ClinicalTrials.gov identifier: NCT01819545.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 34 publications
1
35
0
1
Order By: Relevance
“…The verification experiment indicated 6 miRNAs as the best candidates for further verification in larger cohorts as possible early AD biomarkers. References: * [2046, 57, 8487], # [21, 22, 28, 30, 57, 87]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The verification experiment indicated 6 miRNAs as the best candidates for further verification in larger cohorts as possible early AD biomarkers. References: * [2046, 57, 8487], # [21, 22, 28, 30, 57, 87]. …”
Section: Resultsmentioning
confidence: 99%
“…The source of miRNAs is another important aspect. So far different blood sources were investigated for detection of circulating miRNAs in AD patients: plasma [21, 31, 34, 35, 38, 46, 87], serum [20, 24, 25, 27, 32, 33, 36, 4043], blood mononuclear cells [30], whole blood [22, 8486] and plasma exosomes [29]. All miRNA sources have some advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They exhibit high stability in plasma, serum, urine and saliva (Chen et al, 2008), and can be detected as cell-free or exosome-derived molecules (Mitchell et al, 2008). Recent studies have shown that in CNS diseases such as stroke, Alzheimer’s disease (AD) and glioblastoma, the pathological processes in the brain could be reflected in peripheral miRNA expression patterns (Zeng et al, 2011; Ilhan-Mutlu et al, 2012; Rao et al, 2013; Wang et al, 2015). Thus, plasma miRNA expression levels in PD patients may help us understand the pathological processes in the brains as those aforementioned diseases.…”
Section: Discussionmentioning
confidence: 99%